Bone grafting in small animal orthopaedic surgery. Issue 4 (3rd April 2014) - Innes, John
Abstract : Bone grafting is a useful technique for a variety of orthopaedic injuries, but general practitioners may not routinely use it. This article aims to 'demystify' the subject of bone grafting and provide step‐by‐step guides for the harvest of autogenous cancellous bone grafting (grafts taken from the patient), as well as to provide information on the selection and use of ready‐to‐use allografts (grafts taken from donors of the same species) and other more recent modalities.